1997
DOI: 10.1530/eje.0.1360107
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active human islet amyloid polypeptide/amylin in transgenic mice

Abstract: This study has shown that correctly processed hIAPP produced in transgenic mouse pancreatic beta cells exhibits full biological activity. The results validate these transgenic mice for the study of (patho)physiological roles of hIAPP in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Pancreata were excised and snap frozen (liquid nitrogen) and peptides extracted (homogenization, acid/ethanol) (27). …”
Section: Methodsmentioning
confidence: 99%
“…Pancreata were excised and snap frozen (liquid nitrogen) and peptides extracted (homogenization, acid/ethanol) (27). …”
Section: Methodsmentioning
confidence: 99%
“…A useful experimental model to study the amyloidogenic effects of human amylin and variants is the transgenic mouse that expresses human amylin. Eight research groups have reported the results of studies using this model [35,36,37,38,39,40,41,42]. One general theme, i.e., that the amount of secretion of human amylin determines the level of amyloidosis, was reiterated in a recent paper in which amounts of dietary fat [43] induced islet amyloidosis and impaired insulin secretion.…”
Section: Transgenic Mouse Models That Express Human Amylinmentioning
confidence: 99%
“…The latter were extracted overnight in acidified ethanol, lyophilized and prepared for radioimmunoassay (RIA) (18). The DNA content in tissue pellets was measured (19) as a reference for peptide quantification in the tissue extracts.…”
Section: Tissue and Plasma Extractionmentioning
confidence: 99%
“…Tissue extracts were subjected to reversed-phase HPLC on a Nucleosil 100-7C18 column (Machery-Nagel, Dü ren, Germany) as described previously (18). Mean recoveries of synthetic human IAPP and C-pIAPP were 87.5 Ϯ 9.1% (n = 4) and 91.2 Ϯ 2.9% (n = 2) respectively.…”
Section: Reversed-phase High-performance Liquid Chromatographymentioning
confidence: 99%